Shaykh ‘Abd al-Ra‘ūf al-Fanṣūrī (1615-1693 CE): A Study of His Contribution to the Development of Islamic Education in the Malay World - Arif, Ridwan; Siraj, Fuad Mahbub (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Acheh as one of the earliest centres of the spread of Islam in the Malay Archipelago, had played a significant role in advancing Islamic education in the region. History recorded many scholars who came from Acheh and most of them had great influence, not only in the country, but also in the Malay-Indonesian archipelago. Among the scholars were Ḥamzah Fanṣūrī, Shams al-Dīn al-Sumaṭra’ī, Nūr al-Dīn al-Rānīrī and ‘Abd al-Ra’ūf al-Fanṣūrī. Undoubtedly, these scholars had made significant contributions to the progress of Islamic education in this area. This study aims to investigate the contribution of ‘Abd al-Ra’ūf al-Fanṣūrī in the effort to advance Islamic education in the archipelago in the context of Islamic educational institutions, the development of Islamic knowledge fields and literature, as well as the orientation of Islamic education. This study is based on qualitative research using document analysis methods. The findings of this study show that ‘Abd al-Ra’ūf has played a significant role in advancing Islamic education in the archipelago during the 17th century. Among his efforts in this field were the establishment of Islamic educational institutions, expanding the fields of Islamic knowledge by composing many works on each fields of knowledge, and also by introducing and applying a new orientation of Islamic education which is equilibrium between exoteric (sharī‘ah) and esoteric (Sufism) aspect of Islamic teaching.